Non Functioning Paraganglioma in the Urinary Bladder: a Case Report - Wang, Shangren; Zhang, Aiqiao; Huang, Shiqiao; Ma, Yong; Yang, Yongjiao; Liu, Xiaoqiang; Zhang, Ludong (Urology Journal, 2020)
Paragangliomas are tumors that arise from autonomic nervous system. Non-functioning bladder paraganglioma is rare and usually misdiagnosed. Here we describe a case of a 45-year-old man with primary urinary bladder paraganglioma. The patient had no active signs and symptoms, and histological and immunohistological examinations of a transurethral resection specimen confirmed correct diagnosis. After successful transurethral resection of the tumors, the patient showed no signs of recurrence at one-year follow-up.